2019
DOI: 10.1039/c8nj05878d
|View full text |Cite
|
Sign up to set email alerts
|

Boosting CO2 electroreduction over silver nanowires modified by wet-chemical sulfidation and subsequent electrochemical de-sulfidation

Abstract: Ag nanowires modified by wet-chemical sulfidation and subsequent electrochemical de-sulfidation possess more nanofeatures and enhanced eCO2RR performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Therefore, we concluded that the species that participate CO2RR may be Ag2S-like phase or Ag, which depends on the CO2RR potential. The effect of sulfation [22][23] or Ag-S interaction [4], either positive or negative, on the CO2RR performance can't be excluded, but it will not cover the catalytic advantage of Ag/ZIF-8 over Ag/C because Ag NPs in both catalysts were prepared by using MPA and would not exhibit too many differences. The small-sized Ag NPs (3.9 nm) on ZIF-8 and the possible synergistic effect between Ag NPs and ZIF-8 can account for the catalytic advantage of Ag/ZIF-8 over Ag/C.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we concluded that the species that participate CO2RR may be Ag2S-like phase or Ag, which depends on the CO2RR potential. The effect of sulfation [22][23] or Ag-S interaction [4], either positive or negative, on the CO2RR performance can't be excluded, but it will not cover the catalytic advantage of Ag/ZIF-8 over Ag/C because Ag NPs in both catalysts were prepared by using MPA and would not exhibit too many differences. The small-sized Ag NPs (3.9 nm) on ZIF-8 and the possible synergistic effect between Ag NPs and ZIF-8 can account for the catalytic advantage of Ag/ZIF-8 over Ag/C.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have applied Ag-based catalysts with different sizes andm orphologies as electrode materials for CO 2 RR, due to their high activity and selectivity for CO 2 reduction to CO. For instance, Han and co-workers utilized Ag nanowires for electroreduction CO 2 to CO. [27] In brief, core-shell Ag@AgS nanowires were obtained by aw et-chemical sulfidation process of Ag NWs, and then electrochemically removed sulfide to form de-sulfidated Ag nanowires (DS-Ag NWs, Figure 3a). The surfaceo ft he obtainedD S-Ag NWs was consisted of abundant Ag nanocrystallites, resulting in am ore uneven surface than the originalAgNWs (Figure 3b-d).…”
Section: Ag Catalystsmentioning
confidence: 99%
“…Furthermore, by wrapping with reduced graphene oxide (rGO), the Cu NWs preserved the origi- Reproducedw ith permission. [27] Copyright2 019, The Royal Societyof Chemistry.…”
Section: Cu Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, gold and palladium are improper for large-scale utilization owing to their rarity and costliness [28]. Zinc possesses poorer stability compared with the other three metals [29]. Silver provides an appreciable compromise between expense and performance and is an attractive option.…”
Section: Introductionmentioning
confidence: 99%